Novel Endoscopic Suture Anchor Device for Large Defect Closure Following Endoscopic Submucosal Dissection - Feng, Jiancong; Zhai, Yaqi; Liu, Zhenyu; Linghu, Enqiang (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Feng J, Zhai Y, Liu Z, Linghu E. Novel endoscopic suture anchor device for large defect closure following endoscopic submucosal dissection. Turk J Gastroenterol. Published online October 31, 2025. doi:10.5152/tjg.2025.25240